Cane bagasse ash for manufacture of building materials: preliminary study (2014)
Valle del Cauca, for the environmental conditions, has suitable the sugar-cane-crops. A residue of cane processing, little explored is the ash from bagasse, objective of this study. The cane bagasse ash (CBA) is a by-product from the cane processing, so is pourly explored, being an interesting field to research.  Once is used in industrial boilers, leads to the CBA, the material waste like a coal or fly ash is considered a material with pozzolanic character by some researchers. Three ashes from sugar industries from Valle del Cauca, through chemistry composition, X-ray diffraction and pozzolanic activity were studied. The ashes analyzed, are composed of silica SiO2 and alumina Al2O3 in different proportions and with amorphicity in its structure, which favors the reactivity with cement. The samples were thermally treated due to the high content of unburned, and were determined pozzolanic activity index, which value (until 98%) is complying with the ASTM C618.  With the results it was concluded that this residue may be added to the cement for construction materials. It is suggested further study of mechanical strength and durability.